CREDIT RESTRUCTURITATION IN GRESIK RURAL BANK CORPORATION THE IMPACT OF THE SPREAD OF CORONAVIRUS DISEASE 2019 ON DEBTORS WITH PROBLEM LOANS AFTER APPLIYING POJK NUMBER 48/POJK.03/2020 - Aziyah, Vivi Nur; Kartika, Adhitya Widya (JOSAR (Journal of Students Academic Research), 2024)
This study aims to analyze and understand related to the implementation of credit restructuritation and to find out the obstacles and efforts in implementing credit restructuritation during the Covid- 19 pandemic in Gresik rural Bank corporation. This type of research uses an empirical juridical legal research method, where the source of the data obtained is directly from the field through interviews and obtained from literature studies, this research method is descriptive analytical using a qualitative approach. The results of this research are that in order to overcome bad / problem loans due to the impact of the Covid-19 pandemic, Gresik Rural Bank Corporation implements a restructuring policy by referring to the standard provisions of POJK Number 48/POJK.03/2020. The form of restructuring provided is the provision of a period of approximately 10 months and does not exceed the time limit in accordance with the provisions of the regulation to make interest- only installments, for arrears the principal will be paid after the credit restructuring is completed. The implementation of this credit restructuring did not escape the obstacles faced by PD.BPR Bank Gresik, these obstacles were caused by external factors from the debtor. Even so the PD. BPR